A dark and secret place : a novel - Williams, Jen (Fiction writer) (Crooked Lane, 2021)
"When prodigal daughter Heather Evans returns to her family home after her mother's baffling suicide, she makes an alarming discovery--stacks and stacks of carefully preserved letters from notorious serial killer Michael Reave. The Red Wolf, as he was dubbed by the press, has been in prison for over twenty years, serving a life sentence for the gruesome and ritualistic murders of several women across the country, although he has always protested his innocence. The police have had no reason to listen, yet Heather isn't the only one to have cause to re-examine the murders. The body of a young woman has just been found, dismembered and placed inside a tree, the corpse planted with flowers. Just as the Red Wolf once did."--